Homoeopathic Treatment of Young Females with Subclinical Hypothyroidism: A Prospective Observational Study - Arora, Preeti; Goel, Meetu (Homœopathic Links, 2022)
Introduction Subclinical hypothyroidism (SCH) is defined as elevated levels of serum thyroid-stimulating hormone (TSH) (TSH: 5–20 μIU/mL; normal range: 0.15–3.5 μIU/mL) with normal serum levels of free thyroid hormones mainly free T4 (0.89–1.76 ng/dL). SCH does not affect the development process very much and hence there are no universally accepted recommendations for its treatment but it is important to have optimal thyroid function for normal growth and development in children; it may progress to overt hypothyroidism and other health issues. So, its diagnosis in early stage of life and hence its treatment will definitely benefit the growing children.Objective The objective of this study is to review the role of homoeopathy in SCH in younger aged females.Method Total 212 cases were screened, 54 diagnosed cases of SCH were enrolled on the basis of inclusion criteria and 4 cases dropped out from the study. Total 50 cases were given individualised homoeopathic medicines based on repertorisation of totality of symptoms and in consultation with Materia Medica.Result Results showed significant difference after comparing pre- and post-treatment values using paired t-test; the difference in mean values of Serum TSH values was found to be statistically significant (p-value < 0.00001). At baseline, the mean TSH level was 7.158 μIU/mL which decreased to 4.368 μIU/mL (p < 0.00001).Conclusion This study indicates the positive role of homoeopathic therapy in the management of SCH. Such study with bigger sample size through randomised controlled trial is needed for further validation.
Keywords: homoeopathy; subclinical hypothyroidism; TSH; thyroid hormones